Analisis Kebutuhan dan Perancangan Sistem Informasi Administrasi Kependudukan untuk Meningkatkan Efisiensi Layanan di Kelurahan Paropo - Ismail , Asriani; KH, Musliadi (Fakultas Komputer - Universitas Universal, 2023)
Paropo Subdistrict Office is a subdistrict located in Panakkukang District, Makassar City with a population of approximately 15,932 people. The current information system for population administration services in government agencies, such as the Paropo Subdistrict office, is still carried out semi-computerized, where the preparation of certificates and cover letters still uses Microsoft Word and Microsoft Excel, resulting in less than optimal service to the community. This research aims to provide convenience when processing data and writing correspondence. The systems research method used in this research is the PIECES analysis method (Performance, Informance, Economy, Control, Efficiency, Service). Depicting the system using use case diagrams, activity diagrams, and sequence diagrams. The result of this research is to create a design for a population administration service information system at the Paropo Village office. With this system, it can make it easier to manage data, especially for correspondence purposes, according to what is desired and is more structured and stored properly in the system.